Evaluating the effects of pharmaceutical pollutants on common carp (Cyprinus carpio): histopathological and antioxidant responses - Shaalan, Walaa M.; Idriss, Shaimaa K. A.; Lee, Jae-Seong; Mohamed, Nadia H.; Sayed, Alaa El-Din H. (Frontiers in Physiology, 2025)
IntroductionThe release of pharmaceutical chemicals into aquatic environments has emerged as a significant ecological concern, originating from agricultural runoff, sewage effluents, and improper disposal of medications.MethodsThis study investigates the impacts of four common pharmaceuticals (bromazepam, naproxen, metoprolol, and sotalol) on common carp (Cyprinus carpio), a vital bioindicator species. We evaluated neurological, immunological, and histopathological responses in carp exposed to these pharmaceuticals over 15 days.ResultsNeurological assessments showed significant reductions in acetylcholinesterase (AChE) and monoamine oxidase (MAO) activities, and nitric oxide (NO) levels, indicating potential disruptions in neurotransmission and enzyme function. Immunological analysis revealed elevated levels of pro-inflammatory cytokines interleukin-1β (IL-1β) and interleukin-6 (IL-6), suggesting an inflammatory response. Histopathological examinations identified tissue alterations in the liver, kidney which correlated with the observed biochemical and immune responses.DiscussionThese findings highlight the adverse effects of pharmaceutical contaminants on aquatic species, emphasizing the necessity for comprehensive environmental risk assessments and strategies to mitigate their impact. This study enhances the understanding of pharmaceutical pollutants’ ecological effects, informing policy and conservation efforts to protect aquatic ecosystems.